Inefficiency in self-organized attentional switching in the normal aging population is associated with decreased activity in the ventrolateral prefrontal cortex - Hampshire,A; Gruszka,A; Fallon,SJ; Owen,AM (J Cogn Neurosci, 2008)
Studies of the aging brain have demonstrated that areas of the frontal cortex, along with their associated top-down executive control processes, are particularly prone to the neurodegenerative effects of age. Here, we investigate the effects of aging on brain and behavior using a novel task, which allows us to examine separate components of an individual's chosen strategy during routine problem solving. Our findings reveal that, contrary to previous suggestions of a specific decrease in cognitive flexibility, older participants show no increased level of perseveration to either the recently rewarded object or the recently relevant object category. In line with this lack of perseveration, lateral and medial regions of the orbito-frontal cortex, which are associated with inhibitory control and reward processing, appear to be functionally intact. Instead, a general loss of efficient problem-solving strategy is apparent with a concomitant decrease in neural activity in the ventrolateral prefrontal cortex and the posterior parietal cortex. The dorsolateral prefrontal cortex is also affected during problem solving, but age-related decline within this region appears to occur at a later stage.